2013
DOI: 10.7600/jspfsm.62.141
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular adaptations induced by low load resistance training method with skin cooling

Abstract: Loss of muscle strength is not only associated with loss of muscle mass, but also affected by neural factors. It is well known that facilitatory and inhibitory responses of spinal motor neurons occur with cutaneous stimulation via spinal interneurons. The purpose of this study was to examine the neural adaptations associated with low load resistance training utilizing skin cooling (SC). 10 men trained both legs and each side was randomly assigned to SC training (SC-T) and non SC training (NSC-T). Subjects perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that low-intensity exercises with skin cooling (i.e. 35% maximal voluntary contraction) may increase muscle strength 9) . Cutaneous stimulation with skin cooling has also been shown to modulate polysynaptic neural pathways, and a neural connection between skin cold receptors (transient receptor potential melastatin 8: TRPM8) and the motor neuron pool has been observed [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that low-intensity exercises with skin cooling (i.e. 35% maximal voluntary contraction) may increase muscle strength 9) . Cutaneous stimulation with skin cooling has also been shown to modulate polysynaptic neural pathways, and a neural connection between skin cold receptors (transient receptor potential melastatin 8: TRPM8) and the motor neuron pool has been observed [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Cooling is a simple treatment that can be performed and continued even after an injury. Recently, it has been reported that a combination of training and cooling increased muscle strength enhancement 4) and that continuous daily exposure to a cold environment for a short period inhibited muscle atrophy in microgravity 5) . Moreover, another study found that exposure to a cold environment activated the proteins involved in muscle atrophy 6) .…”
Section: Introductionmentioning
confidence: 99%